MET and FASN as Prognostic Biomarkers of Triple Negative Breast Cancer: A Systematic Evidence Landscape of Clinical Study - Jiang, Weihua; Xing, Xiao-Liang; Zhang, Chenguang; Yi, Lina; Xu, Wenting; Ou, Jianghua; Zhu, Ning (Frontiers in Oncology, 2021)
Background: To know the expression of Mesenchymal-Epithelial Transition factor (MET) and Fatty Acid Synthase (FASN) in Triple Negative Breast Cancer (TNBC) patients, as well as its relationship with clinical pathological characteristic and prognosis. Methods: we used immunohistochemistry staining to detect the expression of MET and FASN for those 218 TNBC patients, and analyze their relationship with the clinical pathological characteristic and prognosis. Results: 130 and 65 out of 218 TNBC patients were positive for MET in the cancer and adjacent tissues respectively. 142 and 30 out of 218 TNBC patients were positive for FASN in the cancer and adjacent tissues respectively. Positive expression of MET and FASN were significantly correlated with lymph node metastasis, pathological TNM, and pathological Stage. In addition, the positive expression of MET and FASN were correlated with recurrence and metastasis. The combined use of MET and FASN can better predict the survival condition. Conclusions, our results indicated that MET and FASN showed good predictive ability for TNBC. Combined use of MET and FASN were recommended in order to make a more accurate prognosis for TNBC.